THE USE OF ELLIPSIS BY CHARACTER ‘HAZEL’ IN “THE FAULT IN OUR STARS” MOVIE SCRIPT - Martha Sondang Mei Morsa Simanjuntak; Sortha Silitonga (State University of Medan, 2015)
Ellipsis is omission of words which has been understood well from the omissionwill not change the meaning of the utterance itself. We can find mostly ellipsis inspoken language. One of spoken languages we can use as the medium in learningellipsis is movie script. One of many great movie scripts is The Fault in Our Starsmovie script by Scott Neustadter& Michael H. Weber. The aim of the research isto find out the use of Ellipsis by ‘Hazel’ in The Fault in Our Stars movie script.This research is descriptive qualitative research since it analyzes the use of ellipsisby ‘Hazel’ in the movie script. The data are the ellipsis which are used bycharacter ‘Hazel’ in each her utterances in The Fault in Our Stars movie scriptfrom 50 scenes. The result of the research shows there are three 124 utterancesconsist of 31 Nominal Ellipsis with 25%, 4 Verbal Ellipsis with 3.23%, and 89Clause Ellipsis with 71.77%. The most dominant type of Ellipsis that used bycharacter ‘Hazel’ in The Fault in Our Stars movie script is Clause Ellipsis with 89total numbers and total percentages 71.77%. It means people in havingconversation want to be as effective as possible since the most complexgrammatical unit is a clause. From this research, I hope the readers, lecturers, andstudents should apply ellipsis appropriately in their daily conversation in order toavoid misunderstanding in the conversation since ellipsis appears mostly in theinformal context and daily conversation.